2022
DOI: 10.1038/s41598-022-13044-0
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of microRNAs and tRNA-derived ncRNAs in mesothelial and mesothelioma cell lines after asbestiform fiber exposure

Abstract: Experimental evidence demonstrated that fluoro-edenite (FE) can develop chronic respiratory diseases and elicit carcinogenic effects. Environmental exposure to FE fibers is correlated with malignant pleural mesothelioma (MPM). An early diagnosis of MPM, and a comprehensive health monitoring of the patients exposed to FE fibers are two clinical issues that may be solved by the identification of specific biomarkers. We reported the microRNA (miRNA) and transfer RNA-derived non coding RNA (tRNA-derived ncRNA) tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Specifically, the inversely regulated tRFs include three 5’ tRF halves that have been implicated in immune related functions (Zorbaz et al , 2022) and may potentially participate in immune reactions related to anxiety and obesity. Of these three 5’ halves, tRF-32-PSQP4PW3FJI01, has been found to be upregulated in breast cancer tumors compared to adjacent normal tissue (Wang et al , 2019), tRF-32-86V8WPMN1E8YN was upregulated in human malignant mesothelioma vs normal mesothelium (Filetti et al , 2022), and tRF-32-87R8WP9N1EWJM has been detected in blood cells (Winek et al , 2020). Thus, tRFs may also take part in the immune system-related inverse regulation observed in anxiety and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the inversely regulated tRFs include three 5’ tRF halves that have been implicated in immune related functions (Zorbaz et al , 2022) and may potentially participate in immune reactions related to anxiety and obesity. Of these three 5’ halves, tRF-32-PSQP4PW3FJI01, has been found to be upregulated in breast cancer tumors compared to adjacent normal tissue (Wang et al , 2019), tRF-32-86V8WPMN1E8YN was upregulated in human malignant mesothelioma vs normal mesothelium (Filetti et al , 2022), and tRF-32-87R8WP9N1EWJM has been detected in blood cells (Winek et al , 2020). Thus, tRFs may also take part in the immune system-related inverse regulation observed in anxiety and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the inversely regulated tRFs include three 5′ tRF halves that have been implicated in immune-related functions [ 48 ] and may potentially participate in immune reactions related to anxiety and obesity. Of these three 5′ halves, tRF-32-PSQP4PW3FJI01 was found to be upregulated in breast cancer tumors compared to adjacent normal tissue [ 94 ], tRF-32-86V8WPMN1E8YN was upregulated in human malignant mesothelioma vs. normal mesothelium [ 95 ], and tRF-32-87R8WP9N1EWJM was detected in blood cells [ 49 ]. Thus, tRFs may also take part in the immune system-related inverse regulation observed in anxiety and obesity.…”
Section: Discussionmentioning
confidence: 99%
“… 20 More details about tRNA-derived ncRNA classification and nomenclature can be found in. 21 , 22 Importantly, it has been shown that tRNA-derived ncRNAs are not mere byproducts of random tRNA cleavage as reported in. 11 , 23 Rather they may actively play roles in several biological phenomena, such as ribosome biogenesis, retrotransposition, virus infections, apoptosis, and cancer pathogenesis.…”
Section: Introductionmentioning
confidence: 88%